Post‐exposure rabies prophylaxis for mass bat exposures: Case series and systematic review. (29th April 2020) - Choe, Young June; Teevan, Bridget; Smit, Michael; Quilliam, Daniela; Bandy, Utpala; Mermel, Leonard
Abstract: To assess and describe the use of rabies post‐exposure prophylaxis (PEP) related to mass bat exposures (MBEs) in the literature and in the state of Rhode Island. Data on MBE events occurring between 2010 and 2016 from the Rhode Island Department of Health (RIDOH) were reviewed to determine PEP usage. For comparison, a systematic review was also performed by searching PubMed, EMBASE, Cochrane Library and Web of Science using the keywords 'rabies, ' 'bat' and 'exposure.' There were three MBE events in Rhode Island between 2010 and 2016 in which groups of individuals were asleep during the potential exposure. As a result, RIDOH provided PEP to those involved in the event. In a systematic review of 12 published reports, a variety of settings were involved in MBEs: camping sites, a domestic flight, a neonatal intensive care unit and dormitories. The number of potential rabies exposures ranged from five to 1, 429 people. PEP recommendations for assessed persons ranged from 0% to 100% across events (median 21%). The variation in PEP recommendations following a MBE may be dependent on medical need, past precedent or preference. Federal guidance for MBE is needed to add clarity and to minimize the variability in PEP recommendations for such events in the future.